(untitled) (Journal of Science and Technology, 2016)
The responses of 192 ready-to-lay chickens (20 wk old) were studied in an 8-month long experiment in which graded levels of cocoa pod-and-husk (CPH) meal were fed Four dietary treatments incorporating 0, 50, 100 and 150g of CPII meal per kg were used and the birds were randomly assigned in equal numbers in a completely randomized design. The diets were isocaloric and isonitrogenous and were fed ad libitum. Water was also provided free choice. While feed consumption significantly increased as dietary CPH levels increased, the efficiency of feed conversion, final body weight and weight gain declined (P < 0.05). None of the other production traits were influenced by CPH level. In addition, CPH had no significant effect on blood parameters including hemoglobin, PCV, total protein, globulin and albumin. The feeding of CPH significantly increased the weight of kidneys, gizzard and intestines.